ANALISIS KADAR HEMOGLOBIN (HB) TERHADAP BALITA STUNTING USIA 6-59 BULAN - Nuraini, Indria; Setyo Iswati, Retno; hartiningtiyaswati, Setiya (Jurnal Kebidanan, 2024)
Anemia and stunting are two different conditions, but both have important determinants and avenues to consider when designing interventions. Stunting and anemia in toddlers in Indonesia has not been widely identified. The detection of stunting and anemia in toddlers makes it easier for health workers to provide treatment. The purpose of this study was to determine hemoglobin levels in stunted toddlers aged 6-59 months. This research used a cross-sectional approach, which was carried out on toddlers aged 6-59 months with stunting. The number of research samples is 16 respondents. Data analysis was tested using univariate and bivariate. For univariate analysis the results of the questionnaire are presented with a frequency distribution table, while for bivariate analysis using a simple linear regression test. Prevalence of stunting based on male sex (68.75%), prevalence aged 13-59 months (81.25%), prevalence of history of exclusive breastfeeding (62.5%), prevalence of food fulfillment does not vary (68.75%) , prevalence of history of Vitamin A (100%), prevalence of history of illness in the last 2 weeks with fever, cough and cold (37.5%). Prevalence of anemia (56.3%) and prevalence of stunting (62.5%). The results of the simple linear regression test are that hemoglobin levels influence stunting by 46.7%. While the output is significant (sig.) 0.004 <0.05. The conclusion of this study is that there is a significant influence on hemoglobin levels on stunting